National Institute of Public Administration (INTAN) / Muhammad Ramzi Mohammad Fauzi - Mohammad Fauzi, Muhammad Ramzi (University Technology MARA Sarawak, 2017)
National Institute of Public Administration is a government agency which responsible for training the civil servants in management and administration. It is popularly known as INTAN (Institut Tadbiran Awam Malaysia). INTAN’s main campus, located at Bukit Kiara Kuala Lumpur was officially opened in 1984 and INTAN Jalan Elmu then became the Central Regional Campus (INTENGAH) in 1998. Increasing demand for INTAN’s training programmes then necessitated the establishment of two other regional campuses. The Sarawak Campus in Kota Samarahan, Sarawak was established in 1999 while the Sabah Campus in Kota Kinabalu, Sabah was set up in 2001. INTAN Sarawak, or formerly known as INTAN Wilayah Timur (INTILA), has been establish as the result of decision of the Cabinet in its meeting on 27 January 1999. The name of INTILA, then being change as INTAN Malaysia Sarawak on 2001, and being change again as INTAN Sarawak on 2009. At this time, INTAN Sarawak has been moved to its own campus in No. 2, Lot 5452, Jalan Datuk Mohammad Musa, 94300 Kota Samarahan which is located 20 km to the northeast ofthe city of Kuching.